Sheikh M. Yasin’s Grave Pilgrimage: Study of Jamaah Tarekat Syattariyah in Tanjung Ampalu, West Sumatera - Anum, Muhammad (UIN Sjech M. Djamil Djambek Bukittinggi, 2024)
The background of this research is the Syattariyah congregation's motivation to perform a grave pilgrimage to the grave of Sheikh M. Yasin in Tanjung Ampalu. The purpose of this research is basically to find out why Syattariyah adherents make a grave pilgrimage to the grave of Sheikh M. Yasin and why the grave of Sheikh M. Yasin becomes an attraction by the followers of the Syattariyah order to be used as a grave pilgrimage activity. The research method used in this study is the descriptive qualitative method. Data collection was done through interviews, observation, and documentation. The research place was conducted at the grave of Sheikh M. Yasin in Tanjung Ampalu. The study participants amounted to 17 people, consisting of the Tarekat Syattariyah congregation, traditional leaders, and tomb managers. The results showed that the congregation of the Syattariyah Order made a pilgrimage to eat Sheikh M. Yasin three times a year, namely Rajab, Safar, and Syaban, to carry out religious activities Yasinan, Zikir, and Wirid. The choice of the grave of Sheikh M. Yasin was influenced by three factors, first because it has Charismatic, secondly the grave and Surau of Sheikh M. Yasin were recorded as Cultural Heritage and included as a Surau of the West Sumatra Syattariyah Tarekat, thirdly because of religious knowledge.